METODE TARJIH IBNU JARIR ATH-THABARI DALAM TAFSIR JAMI’ AL-BAYAN ‘AN TA’WIL AYI AL-QUR’AN - Solihin, Ahmad (Institut PTIQ Jakarta, 2024)
Interpretation of the Qur'an is absolutely necessary to understand the meaning and content of the Qur'an as a guide to life and the lives of Muslims to achieve happiness in this world and in the hereafter. Because only Allah SWT and the Prophet Muhammad SAW know the meaning and content of the Qur'an. It is ath-Thabari whose full name is Muhammad bin Jarir bin Yazid bin Katsir bin Ghalib, sometimes called Abu Ja'far is seen by leading scholars as the main mujtahid. His leadership, breadth of knowledge combined with humility, memory and intelligence are the crown of his asceticism, holiness and piety. In his interpretation as in his monumental work, the book Tafsir Jami'ul Bayan 'an Ta'wil Ayi Al-Qur'an, ath-Thabari uses the method of interpretation of narration (tafsir bi al-Ma'tsur). A method of interpretation based on the approach of the texts of the Qur'an and Hadith. If there is a conflict of interpretation in understanding the meaning and content of the Qur'an, ath-Thabari performs tarjih (excellence) based on 17 tarjih methods, sometimes his opinions are still different from the opinions of other commentators to this day